1964
DOI: 10.1002/zaac.19643320506
|View full text |Cite
|
Sign up to set email alerts
|

Über die Löslichkeit von Lithiumnitrid, Calciumnitrid und Calciumsulfid in geschmolzenen Salzen

Abstract: Die Nitride von Lithium und Calcium sowie Calciumsulfid sind in einer Reihe Alkali‐ und Erdalkalisalzen löslich. Größtes Lösungsvermögen zeigen Lithiumsalze und deren Mischungen. Die Abhängigkeit der Löslichkeit von der Temperatur in den verschiedenen denen Lösungsmitteln wird bestimmt, und die Ergebnisse werden diskutiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

1979
1979
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
1
6
0
3
Order By: Relevance
“…Li 3 N was shown by Glemser et al [12] to be soluble in ionic melts including LiCl, LiBr, and LiF-LiCl eutectic. Other studies [13,14] indicated the formation of low melting temperature eutectics in all of the Li nitride-Li halide systems except for the fluorides.…”
Section: Resultsmentioning
confidence: 96%
“…Li 3 N was shown by Glemser et al [12] to be soluble in ionic melts including LiCl, LiBr, and LiF-LiCl eutectic. Other studies [13,14] indicated the formation of low melting temperature eutectics in all of the Li nitride-Li halide systems except for the fluorides.…”
Section: Resultsmentioning
confidence: 96%
“…Second, the lithium halide seems to be af lux aiding the growth of single crystals without the need for additional NH 4 Cl (Figure 13). This might be correlated with the property of lithium halides of being asolvent for nitrides such as Li 3 N. [77,78] High-pressure metathesis has been shown to offer systematic access to rare-earth nitridophosphates by addition of starting materials such as Li 3 N, P 3 N 5 ,PON,P 2 O 5 ,and/or Li 2 O. Through the addition of Li 3 N, the degree of condensation can be lowered, resulting for example in two M 2 P 3 N 7 polymorphs with M = La, Ce,P r, Nd, Sm, Eu, Ho,Y bc onsisting of tetrahedra single layers with k = 3/7 [Eq.…”
Section: Metathesismentioning
confidence: 96%
“…[77,78] Durch Zugabe weiterer Ausgangsmaterialien wie Li 3 N, P 3 N 5 ,P ON,P 2 O 5 und/oder Li 2 Oe rçffnet die Hochdruckmetathese einen systematischen Zugang zu Seltenerdnitridophosphaten. Erstens stellt die Bildung eines Lithiumhalogenids mit hoher Gitterenergie eine thermodynamische Tr iebkraft fürd ie Bildung des entsprechenden Nitridophosphats dar.Z weitens scheint das Lithiumhalogenid als Fluxmittel zu wirken und so das Wachstum der Kristalle zu verbessern, ohne dass zusätzlich NH 4 Cl bençtigt wird (Abbildung 13).…”
Section: Metatheseunclassified